"La e-administración” el paso de la gestión tradicional a la gestión electrónica - FEIJOO CASADO, Ana María (Revista General de Información y Documentación, 2009)
This article sets the changes in the administration, thus the documents it produces due to the actual legislation and the E.U. directives. It is necessary a change in the archivist job to get used to the new documents and the new ways of recording them.
Keywords: E-administration; Electronic management; Archivists; Records management professionals